Research on the reconstruction of consumers, goods and scenes in new retail based on new technology. Issue 3 (4th September 2020) - Shucui, Wang; Jinjun, Yu; Hongli, Wang
Abstract : The concept of 'new retail' proposed by Alibaba is gradually getting recognised and being practiced by the world‐leading e‐commerce enterprises and traditional retailers, further, it will result in the reconfiguration of retail formats around the world. As a new retail benchmarking enterprise incubated by Alibaba, HEMA fresh has attracted extensive attention from domestic and foreign media and business circles. Based on the typical new retail format of HEMA fresh food initiated by Alibaba, 'fresh supermarket + catering experience + online business warehousing' innovative business model, this study systematically analyses the reconstruction path of new retail format driven by new technology, and finds that customers, goods and scenes are the three leading elements in the reconstruction process of new retail format. These three elements evolve and match with each other under the support of a new technology environment, creating new consumption scenarios for consumers. Finally, this study looks forward to the future of the new retail industry.